Production Potentials of Quality Tree Seeds from Orchards and Plantations in Tanzania - Senya, Fortunate Stephen; Kilawe, Charles Joseph; Nyamoga, Greyson Zabron; Ngaga, Yonika Mathew (Jurnal Manajemen Hutan Tropika, 2025)
Availability of large quantities and high-quality planting materials is essential for sustainability of tree planting and quality forest products. However, there have been no sufficient information on production potential of quality and quantity of tree seeds. We assessed and compared seed production potential and germination capacity of four young (8 -14 years) and matured (15 -48 years) stands of plantations and seed orchards of Tectona grandis and Pinus patula located in different agro-climatic areas of Tanzania. In each seed source, 16 plots, measuring 100 x 100 m, were randomly selected. In each plot, seeds were collected from 30 trees bearing seeds and possessing good characters. Results showed that matured stands of T. grandis and P. patula produced significantly heavier seeds (51.4 kg ha-1) (926.1kg ha-1) than young stands (28.3kg ha-1) (782.6kg ha-1) respectively. The weight of seeds in orchards was significantly lighter (17.2kg/ha) than plantations (62.5kg/ ha) for P. patula whereas for T. grandis, the weight of seeds in orchards was heavier (911.8kg/ha.) than plantations (796.9kg/ha). Seeds from matured sources were significantly heavier than young seed sources (P<0.05). The weight of T. grandis and P. patula seeds were higher in seed orchards than plantations and plantation than seed orchards respectively.